PREDICTORS AND PRACTICES OF SEXUAL AND REPRODUCTIVE HEALTH AMONG ADOLESCENT GIRLS IN LIRA CITY, NORTHERN UGANDA. A CROSS-SECTIONAL STUDY. - Ssembogo, Joseph; Ukoha, Winifred (SJ Insights, 2025)
Background Sexual and Reproductive health among adolescents is an increasing public health concern worldwide. Practices of Sexual and Reproductive Health among Adolescent Girls in Lira City, are reinforced and perpetuated by factors that occur at individual, social, and community, and many others. Therefore, this study aimed to assess the predictors and practices of sexual and reproductive health among adolescent girls in Lira City. Methodology This was a cross-sectional study using quantitative methods, participants were randomly selected by stratified and simple random sampling to have equal representation from all classes. Data was collected using a structured self-administered questionnaire. Data was analyzed using SPSS version 23 and descriptive and inferential statics were generated at univariate, bivariate, and multivariate levels. Results 170 respondents participated in this study with a 100% response rate, the majority of the respondents were aged 18 years. 80(54.8%) senior five, 49(31.5%) Anglican, 70(47.9%) Langi tribe, 123(84.2%) resided in urban areas. The descriptive results showed that 67.1% had poor SRH practices. Logistic regression showed that Class attendance and knowledge of SRH were the predictors of SRH practices among adolescent girls. Being in senior four, five, and six would increase the likelihood of having good practices by 16.4%, 20.0%, and 18.9% respectively compared to lower classes. Conclusion The study findings showed that 60.3% of the adolescent girls aged 18 and 19 years in Lira City 67.1% of them had poor SRH practices. Additionally, the study revealed that attending higher classes and having good knowledge of SRH were predictors of good SRH practices among adolescent girls aged 18 and 19 years in Lira City. Recommendations The schools should collaborate with public health facilities in the region to provide outreach of health education and basic SRH services to adolescent girls in schools to enhance proper SRH practices.